Analysis of the meanings generated by the discourse of two regional newspapers on children and adolescents affected by the Colombian armed conflict - Bohórquez Farfán, Ledis; Bohórquez-Pereira, Giovanni; Molina Valencia, Nelson (Estudios sobre el Mensaje Periodístico, 2017)
The article presents research carried out with regional newspaper Vanguardia Liberal and El Frente under the question on current discursive categories about children affected by the political conflict of the country. The theoretical review confirms few studies in this field as well as the need of this work based on a comprehension of discursive social psychology whose premise is the social construction of reality, and the effects rhetoric has on relationships. The method followed was the analysis of contents of 56 newspapers notes selected using the technique is made week. The results indicate that discursive categories of media build facts referred to situations in children see them involved and omitted the voice of these actors. The use of socio-demographic categories was also found in the construction of stereotypical terms employed for the generalization.